Answer:
The given equation is
log(x-3)·log(x)
---------------------- ≤ 0
log(x-4)
As
,
So, we can write the above equation as
log(x-3)·log(x) ≤ 0 ∧ log(x-4)≥0[ if 1/a≤0, then a≥0]
Now, either log(x-3)≤ 0 ∨ log(x) ≤ 0 ∨ log(x-4)≥0
Now replacing 0 by
.
The above equation becomes
log(x-3)≤
∧ log(x) ≤
∧ log(x-4)≥
![\log1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tsnzltwfl29axebjosuxxrhf7r301gy2c9.png)
Cancelling log from both sides of all the three equations
⇒ x-3≤1 ∧ x≤1 ∧ x-4≥1
⇒x≤4 ∧ x≤1 ∧ x≥5
[ if,
this expression has no meaning, so for this expression to exist,
]
Combining all the three solution , the result of the equation is
0≤ x≤1 for
![\log x \text {and } x> 4 for (\log(x-3))/(\log(x-4))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3yz8fdptqvuv4858jkb0mlonb529lkk21l.png)
Why i have written this because the whole expression should be less than zero, so when 0≤ x≤1 ,
becomes negative and when x>4 the expression
will be positive.